2002
DOI: 10.1053/jhep.2002.33993
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of donor age to the recent decrease in patient survival among HCV-infected liver transplant recipients

Abstract: Recurrent hepatitis occurs in the majority of patients undergoing liver transplantation for hepatitis C virus (HCV) cirrhosis, with progression to cirrhosis in up to 30% after 5 years. Based on these data, a decrease in survival can be anticipated with prolonged follow-up. Furthermore, posttransplantation HCV-fibrosis progression has been shown in recent years to increase. Our aims were (1) to describe the natural history of HCV-infected recipients, particularly to determine whether survival has decreased in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
541
10
20

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(616 citation statements)
references
References 15 publications
45
541
10
20
Order By: Relevance
“…[14][15][16][17][18] Only 3 trials have enrolled over 100 patients per arm. [19][20][21] The observational study of 283 HCV-positive liver transplant recipients by Berenguer and colleagues showed that use of tacrolimus compared to CsA-ME was independently associated with development of cirrhosis by multivariate analysis (P ϭ 0.009). 19 Ghobrial et al reported a shorter time to HCV recurrence with tacrolimus, 20 while other researchers have identified a trend suggesting that immunosuppressive treatment with tacrolimus could promote the early induction of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Only 3 trials have enrolled over 100 patients per arm. [19][20][21] The observational study of 283 HCV-positive liver transplant recipients by Berenguer and colleagues showed that use of tacrolimus compared to CsA-ME was independently associated with development of cirrhosis by multivariate analysis (P ϭ 0.009). 19 Ghobrial et al reported a shorter time to HCV recurrence with tacrolimus, 20 while other researchers have identified a trend suggesting that immunosuppressive treatment with tacrolimus could promote the early induction of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Through randomized, blinded fashion we matched each case with its corresponding control based on specific characteristics that previous studies have demonstrated to most likely influence clinical outcomes. 18,21 In order of importance, these variables included donor age (within 10 yr), year of transplantation (within 4 yr), United Network for Organ Sharing/Model for End-Stage Liver Disease score, and recipient age (within 20 yr). Donor age has shown to impact survival after liver transplantation in HCV and thus was chosen as a matching variable.…”
Section: Matched Analysismentioning
confidence: 99%
“…More recently, donor age Ն50 yr has specifically been found to have a negative impact on both patient and graft survival as well as accelerating fibrosis progression and the progression to cirrhosis. [16][17][18] There have been no studies to date examining the impact of donor age on liver transplantation using HCVϩ donor livers.…”
mentioning
confidence: 99%
“…Donor age seems to influence graft survival only in HCVpositive patients. However, there is little chance that this will change, since very few transplant programs are able to pair younger donors with HCV-positive receptors [11,12].…”
Section: Donor and Receptor Factorsmentioning
confidence: 99%